The poetics of displacement: Self-translation among contemporary Russian-American poets. Issue 2 (4th May 2018) - Wanner, Adrian
ABSTRACT: This article explores the practice of self-translation by two bilingual Russian-American poets, Andrey Gritsman and Katia Kapovich. A close reading of some of their self-translated texts elucidates the idiosyncratic nature of self-translation and its poetics of displacement. For both Gritsman and Kapovich, translating their own work becomes a means of exploring the mutation of the self through time, migration, and changing linguistic and cultural environments. A significant difference between the two authors concerns the way in which they present their poems. Gritsman invites a comparison between source and target text and the gaps between them in a bilingual en face edition, whereas Kapovich camouflages her self-translated poems as English originals. In spite of the different staging and performance of self-translation, both poets – by stressing difference rather than similarity in translation – turn their self-translated texts into a metacommentary on their own shifting transnational identities.